Dallo spazio al territorio: Un sistema per l’Osservazione della Terra in tempo reale - Spinetti, Claudia; Doumaz, Fawzi; Buongiorno, Fabrizia (GEOmedia, 2010)
From space to land: a real time Earth Observation system from INGV Since many years INGV (Istituto Nazionale di Geofisica e Vulcanologia) in collaboration with several national and international research institutes, contributes to develop new spatial technologies dedicated to volcano, earthquake and environmental monitoring according to GMES (Global Monitoring for Environment and Security) guide lines in a national and European context. In order to maintain and increase such volcano survey, already operative since several years, a technological investment has been allocated in the context of the convention with the Italian Civil Protection (2007-2009). The new system allows to improve the real time acquisition of remote sensing data for different geophysical applications in the Mediterranean basin and in Central Europe.